Papers of John Smith (as filmed by the AJCP) [M1135] - Smith, John, Surgeon; Australian Joint Copying Project; National Library of Australia; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1950)
Diary kept by John Smith, surgeon on the convict ship Clyde, on a voyage from Dublin to Sydney, via the Cape of Good Hope, April-September 1838.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M1135.
Available also as manuscript.
Also available online
Keywords: Smith, John -- Surgeon, -- Diaries; Clyde (Convict ship).; Ship physicians -- Ireland -- Diaries; Voyages and travels; Transportation of convicts -- New South Wales